Powering ≈50 µm Motion by a Molecular Event in DNA Crystals. Issue 26 (23rd May 2022) - Zheng, Mengxi; Li, Zhe; Zhang, Cuizheng; Seeman, Nadrian C.; Mao, Chengde
Abstract: A major challenge in material design is to couple nanoscale molecular and supramolecular events into desired chemical, physical, and mechanical properties at the macroscopic scale. Here, a novel self‐assembled DNA crystal actuator is reported, which has reversible, directional expansion and contraction for over 50 μm in response to versatile stimuli, including temperature, ionic strength, pH, and redox potential. The macroscopic actuation is powered by cooperative dissociation or cohesion of thousands of DNA sticky ends at the designed crystal contacts. The increase in crystal porosity and cavity in the expanded state dramatically enhances the crystal capability to accommodate/encapsulate nanoparticles/proteins, while the contraction enables a "sponge squeezing" motion for releasing nanoparticles. This crystal actuator is envisioned to be useful for a wide range of applications, including powering self‐propelled robotics, sensing subtle environmental changes, constructing functional hybrid materials, and working in drug controlled‐release systems. Abstract : A major challenge in material design is to translate molecular events to macroscale properties. In this work, self‐assembled DNA crystals are shown to reversibly expand and contract over 50 μm in response to versatile stimuli.